Narrowing inequalities in infant mortality in Southern Brazil - Marcelo Zubaran Goldani; Rosange Benatti; Antônio Augusto Moura da Silva; Heloisa Bettiol; Joel Cristiano Westphal Correa; Marcos Tietzmann; Marco Antonio Barbieri
OBJECTIVE: To determine the trends of infant mortality from 1995 to 1999 according to a geographic area-based measure of maternal education in Porto Alegre, Brazil. METHODS: A registry-based study was carried out and a municipal database created in 1994 was used. All live births (n=119,170) and infant deaths (n=1,934) were considered. Five different geographic areas were defined according to quintiles of the percentage of low maternal educational level (<6 years of schooling): high, medium high, medium, medium low, and low. The chi-square test for trend was used to compare rates between years. Incidence rate ratio was calculated using Poisson regression to identify excess infant mortality in poorer areas compared to higher schooling areas. RESULTS: The infant mortality rate (IMR) decreased steadily from 18.38 deaths per 1,000 live births in 1995 to 12.21 in 1999 (chi-square for trend p<0.001). Both neonatal and post-neonatal mortality rates decreased although the drop seemed to be steeper for the post-neonatal component. The higher decline was seen in poorer areas. CONCLUSION: Inequalities in IMR seem to have decreased due to a steeper reduction in both neonatal and post-neonatal components of infant mortality in lower maternal schooling area.